EU diversity in terms of digitalization on the labor market in the Post-COVID-19 context - Georgiana-Alina Crisan; Madalina Ecaterina Popescu; Eva Militaru; Amalia Cristescu (Economies, 2023)
Digital technologies are being integrated into everyday life worldwide, constantly transforming our society and labor markets. The EU requires digitally smart people in the labor market and has promoted this through the Digital Agenda. In this context, our paper aims to investigate the diversity of the EU member states in terms of the digitalization of the labor market in the post pandemic context. Using a multidimensional perspective, we considered indicators reflecting not only labor market specificities but also the degree of digitalization and the impact of the COVID-19 pandemic. First, the strength of the association between digitalization and the labor market indicators was quantified through a Pearson test, while the cluster analysis highlighted some patterns for the high-tech EU economies compared to the medium- and low-tech EU economies. Among the high-tech economies cluster, Finland stands out as the frontrunner in the EU's digital transformation, with the most digitally skilled workers. At the opposite pole are the South-Eastern countries, which have the most to do to recover and still lack an effective digital policy framework to support youth workers' access to digital training. The practical implications of our study consist mostly of providing decision-makers with directions on issues to tackle when implementing EU digital policies.
Keywords: 330; digitalization; youth employment; labor cost; labor productivity; cluster analysis; COVID-19impac